Fabrication and Characterization of Sub 5 nm Iron Nanoparticles Deposited on Boehmite, Alumina and Kaolinite Nanoplatelets - Chen, Xinlong (Université d'Ottawa / University of Ottawa, 2020)
There is a need for new methods of energy production, from sources of any origin, that do not involve the production of carbon dioxide. Hydrogen is increasingly viewed as a promising fuel for transportation. Hydrogen has a high energy density and can replace a significant portion of our fossil fuel consumption. The overwhelming majority of hydrogen produced today (96%) is derived from fossil fuels. Methane has the highest hydrogen-to-carbon molecular ratio of all fossil fuels and is the best raw material for hydrogen production. Direct methane cracking is a reaction that produces hydrogen gas and solid carbon without the production of carbon dioxide. Magnetite nanoparticles were synthesized using a wet chemical co-precipitation approach with the application of surfactants at selected concentrations. These particles were deposited on various nanoplatelet supports such as boehmite, alumina and kaolinite. Transmission electron microscopy (TEM) and image software were used to characterize the iron oxide nanoparticle morphology and to determine the iron oxide nanoparticle diameters. In-situ Energy-Dispersive X-ray Spectroscopy (EDS) was used to detect the existence of aluminum, iron, silicon and oxygen elements in the sample. X-ray diffraction (XRD) spectroscopy was used to determine the composition of each iron oxide(s)-substrate complex. Sixty five percent of the unsupported magnetite nanoparticles produced measured less than 5 nm. The nanoparticles deposited on boehmite had 41% of their diameters less than 5 nm. Those co-synthesised with magnetite-boehmite had 81% of their diameters less than 5 nm. When co-synthesized, magnetite nanoparticles and boehmite were observed not to precipitate simultaneously due to the different pH of precipitation of their hydroxides. The nanoparticles deposited on kaolinite had rectangular and circular morphologies. It was found that magnetite nanoparticles deposited on boehmite tend to locate around the perimeter of the nanosheet. Calcination was shown to increase nanoparticle diameters due to nanoparticle coarsening. Kaolinite delamination was also studied. Kaolinite was ultrasonicated at 30, 40, 50 and 100% power near the solubility of the urea and surfactants. The kaolinite delaminated under the presence of a surfactant was found to have few fractured platelets compared to the results of exfoliation reported in the literature. Heterogenous magnetite nanoparticles (both deposited and co-synthesized on the substrate) were used in the Fenton degradation reaction of methyl orange. A series of experiments demonstrated that individual stand-alone magnetite nanoparticles with hydrogen peroxide had the fastest degradation rate, while the calcined batches of catalyst-substrate complex have no or miniscule Fenton degradation reaction of methyl orange. Boehmite nanoplatelets were found to act as catalysts in the Fenton reaction. The results were in agreement with the observation that calcination lead to the formation of hematite and maghemite which are not Fenton catalysts. This work was successful in demonstrating that sub 5 nm iron nanoparticles, with the potential to lead to base growth CNTs, can be made and deposited on open nanoplatelet substrates. All metal oxides produced in this work; magnetite, hematite and maghemite can be used to synthesize CNTs. These catalysts have the proper characteristics to be useful in methane cracking where hydrogen and solid carbon can be produced without the release of carbon dioxide.
Keywords: Kaolinite; exfoliation; delamination; ultrasonication; urea; surfactants; CTAB; PVP K30; PVP-10; sodium cholate; magnetite nanoparticle; kaolinite; boehmite; twinned alumina nanosheet; wet chemical synthesis; co-precipitation